Type 2 diabetes and risk for periodontal disease: a role for dental health awareness - H. Jansson (journal of clinical periodontology, 2006)
Background: Several studies have found correlations between diabetes and an increased prevalence of periodontitis. Objective: To analyse, in a group of subjects with type 2 diabetes (T2D), (i) the association between medical characteristics and severe periodontal disease and (ii) dental care habits and knowledge of oral health. Methods: One hundred and ninety-one subjects with T2D were examined. Based on assessment of marginal bone height in panoramic radiographs, two periodontal subgroups were identified: one periodontally diseased (PD1) and one periodontally healthy (PD ) group. All subjects completed a questionnaire about their medical and oral health. Results: Twenty per cent of the subjects were classified as PD1. This was verified by clinical parameters. PD1 individuals had higher haemoglobin A1c (HbA1c) levels ( p50.033) and higher prevalences of cardiovascular complications (p50.012). They were also less likely to be of Scandinavian origin ( p50.028) and more likely to smoke ( po0.001) than the PD- group. The PD1 group rated their oral health as poor ( po0.0001) and believed that T2D had an influence on their oral status ( po0.0001). Conclusion: The best predictor for severe periodontal disease in subjects with T2D is smoking followed by HbA1c levels. T2D subjects should be informed about the increased risk for periodontal disease when suffering from T2D.